Energy access sustainability criteria definition for Colombian rural areas (2023)
Access to energy has long been a subject of interest for governments due to its pivotal role in advancing human progress and well-being. Colombia, like many other nations, faces the challenge of addressing the energy deficit experienced by communities within its jurisdiction. This research endeavor undertakes a comprehensive review of relevant literature pertaining to the sustainability of energy access, with a particular focus on the distinctive circumstances encountered in Non-Interconnected Zones. Through this review, an exhaustive examination of all significant dimensions of sustainability within the national context is conducted. The findings underscore the indispensability of formulating appropriate indicators to accurately assess the realities faced by these underserved populations, while concurrently safeguarding cultural and environmental heritage. The establishment of such indicators is poised to facilitate a comprehensive evaluation framework that duly recognizes the unique contextual factors influencing these communities' sustainable development across various dimensions